Exponential Weight Moving Average (EWMA) Control Chart for Quality Control of Crude Palm Oil Product - Febrina, Wetri; Fitriana, Widya (International Journal of Management and Business Applied, 2022)
In several cases of product quality control in manufactur industries, data that has a small average shift is found due to autocorrelated data, which is a state where the data currently taken is influenced by previous data. The commonly used control chart - the Shewhart control chart, does not show the real situation in the company. The Exponential Moving Weight Average (EMWA) control map is used as an alternative control map to detect small average shifts. In measurement of quality of Crude Palm Oil Product, such as Free Fatty Acid content and level of Colour, where the sampling points are the same, or the samples used are the same, but are collected at different times, this situation could happen. As a result, predictions based on control charts are sometimes not in accordance with real conditions. This study aims to compare the EMWA control chart with the Shewart control chart in analizing the quality of a product. The product used was crude palm oil (CPO) with a case study data from PT X laboratories, a palm oil processing company in Dumai, Riau. We compared the performance of EWMA Control Chart with basic Shewart Control Chart and found that EWMA Control Chart give best performance and much shorter of out of control data.